Functional classification of small towns in Germany. A methodological comparison - Philipp Gareis; Antonia Milbert (Raumforschung und Raumordnung, 2020)
The development of small towns in Germany in terms of their economic, demographic and social endowment is a subject area that has been rather neglected so far. What is more, research often focuses exclusively on small towns in rural and peripheral regions, because this is the only place where they are assigned a certain role. Small towns in central areas, on the other hand, are subsumed under suburbia in research and are thus rarely considered in terms of their specific functions. In this paper, all small towns in Germany are classified with regard to important functions. The typification is done by means of a cluster analysis based on central factors, which in turn are tied to a broad set of indicators. Reference points are the classical method of principal component analysis and, as an alternative method, to geographically weighted principal component analysis. The methodological comparison shows that the alternative method – also due to the high computational effort – is not yet a suitable method for describing spatial relationships between the variables and for small towns with regard to existing functions in their surrounding areas. On the other hand, the approach of the principal component analysis, cluster analysis and discriminant analysis, which is found in the literature, produces well defined and explainable solutions for the formation of different types of small towns in Germany.